FAKTOR RISIKO HIPERTENSI PADA KELOMPOK UMUR ≤45 DI PUSKESMAS PB SELAYANG II TAHUN 2023 - Cristiana, Eva; Nababan, Donal; Sitorus, Mido Ester J; Ginting, Daniel; Manurung, Jasmen (Universitas Budi Darma, 2024)
Hypertension, a silent killer disease, stands as a leading cause of mortality worldwide and a significant health concern in Indonesia. Individuals with hypertension exhibit systolic and diastolic blood pressure levels surpassing 140 mmHg and/or 90 mmHg, contributing to its high prevalence—a major global public health challenge today. This study aimed to establish correlations between age, family history, smoking habits, physical activity, and obesity concerning hypertension incidence at the PB Selayang II Community Health Center in Medan City, North Sumatra. Employing an analytical survey method with a case-control design, the research focused on a population of 70 individuals under 45 years old. Random sampling yielded 35 cases and 35 controls. Primary data collection involved interviews, blood pressure measurements, and height and weight assessments. Secondary data were sourced from Medical Records (RM) at the PB Selayang II Community Health Center. Data analysis employed the chi-square test with a significance level of p0.05 for identifying significant variables, and Odds Ratio (OR) values for quantifying the strength of associations. The results underscored age (p=0.008), family medical history (p=0.004), smoking habits (p=0.002), physical activity (p=0.000), and obesity (p=0.000) as factors significantly linked to hypertension incidence. Consequently, promoting lifestyle changes—such as maintaining a healthy diet to prevent obesity, avoiding smoking, and increasing physical activity—emerges as crucial advice for the public. Furthermore, the implementation of a weight control program at the health center is recommended, given obesity's predominant association with hypertension occurrence